Manufacturing method of artificial graphite material for negative electrode of lithium ion secondary battery, artificial graphite material for negative electrode of lithium ion secondary battery, negative electrode for lithium ion secondary battery, and lithium ion secondary battery
The controlled production of artificial graphite for lithium-ion battery negative electrodes addresses rapid charging issues by minimizing lithium metal formation, ensuring stable discharge capacity and cycle life.
Patent Information
- Application Number
- JP2021101704
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-06-18
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2041-06-18
AI Technical Summary
Lithium-ion secondary batteries using graphite as a negative electrode material face challenges with rapid charging, leading to lithium metal precipitation, reduced lithium ion mobility, and decreased cycle characteristics due to the formation of lithium metal on the electrode surface.
A manufacturing method for artificial graphite materials involves controlling the particle size, surface structure, and chemical composition of the negative electrode by adjusting the heat treatment and grinding processes to minimize lithium metal formation, achieving a volatile content less than 3.71% and a true density of 1.22-1.73 g/cm³, with an average particle diameter of 3.1-11.8 μm.
The method results in lithium-ion batteries with stable discharge capacity even under rapid charging conditions, preventing lithium metal deposition and maintaining capacity over repeated cycles.
Smart Images

Figure 0007623229000003 
Figure 0007623229000001 
Figure 0007623229000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing an artificial graphite material for a negative electrode of a lithium ion secondary battery, an artificial graphite material for a negative electrode of a lithium ion secondary battery, a negative electrode for a lithium ion secondary battery, and a lithium ion secondary battery. [Background technology]
[0002] Lithium-ion secondary batteries are used in automobiles and for industrial purposes such as power storage in grid infrastructure. Graphite such as artificial graphite material is used as the negative electrode material of lithium ion secondary batteries (see, for example, Patent Document 1). Since lithium-ion secondary batteries began to be used as part of social infrastructure, there has been a particular demand for rapid charging characteristics. For example, when applied to electric vehicles (BEVs), (i) the shorter the time required for full charging, the higher the utilization rate of power stations, and (ii) the improved efficiency of braking energy regeneration (improved power consumption) increases the driving range per charge, improving convenience for users. Furthermore, when applied to grid-connected natural energy applications, the larger the allowable charging current, the higher the efficiency of storing natural energy, which can contribute to improving the power generation capacity. However, lithium-ion secondary batteries that use graphite as the negative electrode material have a problem in that lithium metal is easily precipitated on the negative electrode during rapid charging. When lithium metal is precipitated on the negative electrode, the number of lithium ions that can move between the positive and negative electrodes decreases, and the capacity of the lithium-ion secondary battery deteriorates.
[0003] When a lithium-ion secondary battery using a graphite material for the negative electrode is rapidly charged with a large current, lithium metal is electrolytically deposited on the surface of the graphite particles in the negative electrode, resulting in a deterioration in cycle characteristics. To address this problem, various measures have been taken.
[0004] For example, the nonaqueous electrolyte battery described in Patent Document 2 combines a positive electrode made of a positive electrode active material having an olivine crystal structure with a negative electrode to which inorganic oxide nanoparticles have been added. It is disclosed that this improves the Li acceptance of the negative electrode, suppressing Li deposition on the negative electrode surface during rapid charging, which has been a problem with batteries having olivine-based positive electrodes, and dramatically improving cycle characteristics under high loads.
[0005] Patent Document 3 also discloses a nonaqueous electrolyte secondary battery in which graphite powder having an average particle size of 1 to 10 μm is disposed in the surface layer of the negative electrode, graphite powder having an average particle size of 10 to 30 μm is disposed in the layer in contact with the negative electrode current collector, and the proportion of the graphite powder having an average particle size of 1 to 10 μm is 10 to 40% by weight of the total graphite. It is disclosed that this nonaqueous electrolyte secondary battery is excellent in capacity characteristics and cycle life characteristics during high-rate discharge, and further, a nonaqueous electrolyte secondary battery having excellent safety can be provided. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Patent No. 5415684 [Patent Document 2] JP 2009-54469 A [Patent Document 3] Japanese Patent Application Publication No. 10-027600 Summary of the Invention [Problem to be solved by the invention]
[0007] In recent years, lithium ion secondary batteries have begun to be used as social infrastructure such as electric vehicles and natural energy grid interconnection applications. Therefore, lithium ion batteries and their anode graphite materials suitable for even higher current charge acceptance are desired. Anodes made using the above-mentioned conventional anode graphite materials are still insufficient in terms of high current charge acceptance and the like to meet these requirements.
[0008] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide a method for producing an artificial graphite material for a lithium ion secondary battery negative electrode, which enables the production of a negative electrode for a lithium ion secondary battery that is resistant to deterioration in discharge capacity even when charge and discharge cycles are repeated at a large current, an artificial graphite material for a lithium ion secondary battery negative electrode obtained by the production method, a lithium ion secondary battery negative electrode produced from the graphite material, and a lithium ion secondary battery having the negative electrode. [Means for solving the problem]
[0009] As a result of extensive research, the inventors have discovered that by producing raw coal powder with a relatively large specific surface area and a volatile content and true density within specific ranges, and controlling the average particle diameter of the artificial graphite material for lithium-ion secondary battery negative electrodes finally obtained using this raw coal powder to a specific size, a surface superstructure with an appropriate structure is formed on the particle surface, and even if a rapid intercalation reaction of lithium ions occurs (even when rapid charging is performed), no electrodeposition of lithium metal occurs, and therefore deterioration of discharge capacity can be suitably suppressed even when charge-discharge cycles are repeated at large currents, thereby completing the present invention. Specifically, the present invention employs the following configuration.
[0010] [1] A method for producing an artificial graphite material for a lithium-ion secondary battery negative electrode, comprising the steps of: coking a raw oil composition by a delayed coking process to produce a raw coke composition; heat-treating the raw coke composition to obtain a heat-treated raw coke composition; pulverizing the heat-treated raw coke composition to obtain a raw coke powder; and graphitizing the raw coke powder to obtain an artificial graphite material for a lithium-ion secondary battery negative electrode, wherein the raw coke powder has a volatile content of less than 3.71% and a true density of 1.22 g / cm. 3 Super 1.73g / cm 3 and the average particle diameter of the artificial graphite material for a lithium ion secondary battery negative electrode as measured by a laser diffraction particle size distribution analyzer is less than 12.6 μm. [2] The method for producing an artificial graphite material for a lithium ion secondary battery negative electrode according to [1], wherein the maximum temperature reached in the heat treatment in the step of obtaining the heat-treated raw carbon composition is 500°C or higher and 700°C or lower. [3] The method for producing an artificial graphite material for a lithium ion secondary battery negative electrode according to [1] or [2], wherein the raw oil composition has a normal paraffin content of 5 to 20 mass% based on the total amount of the raw oil composition, and an aromatic index fa determined by the Knight method of 0.3 to 0.65. [4] The method for producing an artificial graphite material for a lithium ion secondary battery negative electrode according to any one of [1] to [3], wherein the average particle diameter of the artificial graphite material for a lithium ion secondary battery negative electrode is 3.1 μm or more and 11.8 μm or less.
[0011] [5] An artificial graphite material for a negative electrode of a lithium ion secondary battery, obtained by the production method according to any one of [1] to [4]. [6] A negative electrode for a lithium ion secondary battery, comprising the artificial graphite material for a lithium ion secondary battery negative electrode according to [5]. [7] A lithium ion secondary battery comprising the negative electrode for lithium ion secondary batteries according to [6]. Effect of the Invention
[0012] According to the present invention, it is possible to provide a method for producing an artificial graphite material for a lithium ion secondary battery negative electrode, which can produce a negative electrode for a lithium ion secondary battery that is resistant to deterioration in discharge capacity even when charge and discharge cycles are repeated at a large current, an artificial graphite material for a lithium ion secondary battery negative electrode obtained by the production method, a lithium ion secondary battery negative electrode produced from the graphite material, and a lithium ion secondary battery having the negative electrode. [Brief description of the drawings]
[0013] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an example of a lithium ion secondary battery of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The method for producing an artificial graphite material for a lithium ion secondary battery negative electrode, the artificial graphite material for a lithium ion secondary battery negative electrode, the lithium ion secondary battery negative electrode, and the lithium ion secondary battery according to the present invention will be described in detail below. Note that the present invention is not limited to the following embodiments.
[0015] (Method of manufacturing artificial graphite material for negative electrodes of lithium-ion secondary batteries) The manufacturing method of the artificial graphite material for the negative electrode of a lithium-ion secondary battery of this embodiment includes a step of coking a raw oil composition by a delayed coking process to produce a raw coke composition (hereinafter also referred to as "step A"), a step of heat-treating the raw coke composition to obtain a heat-treated raw coke composition (hereinafter also referred to as "step B"), a step of pulverizing the heat-treated raw coke composition to obtain raw coke powder (hereinafter also referred to as "step C"), and a step of graphitizing the raw coke powder to obtain an artificial graphite material for the negative electrode of a lithium-ion secondary battery (hereinafter also referred to as "step D").
[0016] <About Process A> Step A is a step of coking the feed oil composition by a delayed coking process to produce a feed coal composition.
[0017] A specific example of the feed oil composition in step A is heavy oil. Examples of heavy oils include bottom oils of fluid catalytic cracking oil (FCC DO), heavy oils that have been subjected to advanced hydrodesulfurization treatment, vacuum distillation residual oil (VR), coal liquefaction oil, coal solvent extraction oil, atmospheric distillation residual oil, shale oil, tar sand bitumen, naphtha tar pitch, coal tar pitch, ethylene bottom oil, and the like. The feed oil composition in step A may be one obtained by subjecting the heavy oil to various treatments such as hydrorefining.
[0018] As the feed oil composition in step A, among the above, it is preferable to use heavy oil which contains an appropriate amount of aromatic components and an appropriate amount of normal paraffins and has been subjected to advanced hydrodesulfurization treatment. In addition, when the stock oil composition contains heavy oil, a single heavy oil may be used, or two or more kinds of heavy oils may be mixed and used. When two or more kinds of heavy oils are mixed and used as the stock oil composition, the blending ratio of each heavy oil can be appropriately adjusted according to the properties of each heavy oil. The properties of each heavy oil vary depending on the type of crude oil, the processing conditions until the heavy oil is obtained from the crude oil, etc.
[0019] As the raw material oil composition in step A, among the above, a heavy oil containing a component that generates a good bulk mesophase during coking treatment and a component that generates a gas that reduces the size of the bulk mesophase when the bulk mesophase is polycondensed to carbonize and solidify is preferred.
[0020] <Components that produce good bulk mesophase during coking treatment> An example of a component that forms a good bulk mesophase during coking treatment is a component whose aromatic index fa determined by the Knight method is within a predetermined range. Specifically, the component is preferably a component whose aromatic index fa determined by the Knight method is 0.30 to 0.65, more preferably a component whose aromatic index fa is 0.35 to 0.60, and even more preferably a component whose aromatic index fa is 0.40 to 0.55.
[0021] In this specification, the "aromatic index fa" is the aromatic carbon fraction determined by the Knight method. In the Knight method, the distribution of carbon is 13 The spectrum of aromatic carbon by C-NMR is divided into three components (A1, A2, A3). Here, A1 is the number of carbon atoms in the aromatic ring (the number of substituted aromatic carbons and half of the unsubstituted aromatic carbons ( 13 C-NMR peak of about 40-60 ppm), and A2 is the remaining half of the unsubstituted aromatic carbon ( 13 C-NMR peak of about 60 to 80 ppm), and A3 is the number of aliphatic carbon atoms ( 13(This corresponds to a peak at about 130 to 190 ppm in C-NMR.) The aromatic index fa is calculated by using A1, A2, and A3 as fa = (A1 + A2) / (A1 + A2 + A3). 13 The C-NMR method is the best method for quantitatively determining fa, which is the most basic quantity of the chemical structure parameters of pitches, as shown, for example, in the literature ("Characterization of Pitch II. Chemical Structure" by Yokono and Sanada, Tanso, 1981 (No. 105), pp. 73-81).
[0022] <<A component that generates gas that reduces the size of the bulk mesophase when the bulk mesophase undergoes polycondensation, carbonization, and solidification>> A specific example of a component that generates a gas that reduces the size of the bulk mesophase when the bulk mesophase is polycondensed and carbonized and solidified is normal paraffin.
[0023] The normal paraffin content in the stock oil composition in step A is preferably from 5 to 20 mass %, more preferably from 10 to 15 mass %, based on the total amount of the stock oil composition.
[0024] In this specification, the "normal paraffin content" refers to a value measured by a gas chromatograph equipped with a capillary column. Specifically, after calibration using a standard substance for normal paraffin, a sample of non-aromatic components separated by elution chromatography is passed through the capillary column and measured. From this measurement, the normal paraffin content based on the total amount of the feedstock oil composition can be calculated.
[0025] Normal paraffin contained in the raw oil composition generates gas during coking. This gas plays an important role in restricting the size of the bulk mesophase generated during coking to a small size, and restricting the mesophase to a small size. The gas generated during coking also has the function of uniaxially orienting adjacent mesophases restricted to a small size to form a fine structure with selective orientation.
[0026] When the normal paraffin content of the raw oil composition is 5% by mass or more, the bulk mesophase is inhibited from growing more than necessary, and hexagonal carbon planar laminates of appropriate size are more likely to be formed. Furthermore, when the normal paraffin content in the base oil composition is 20 mass % or less, the amount of gas generated from normal paraffins becomes more appropriate. If excessive gas is generated during the coking process, the unevenness on the outermost surface of the particles caused by the pulverization after the heat treatment of the raw coal composition is likely to grow significantly, and even after graphitization, the atoms on the outermost surface of the particles will be difficult to rearrange into a surface superstructure suitable for rapid charging, which is undesirable.
[0027] Of the above, the feed oil composition in step A preferably has an aromatic index fa determined by the Knight method of 0.30 to 0.65, more preferably 0.35 to 0.60, and even more preferably 0.40 to 0.55.
[0028] When the aromatic index fa of the raw material oil composition in step A is 0.3 or more, the combination of the heat treatment of the raw material coal composition and the subsequent crushing treatment makes it easier to form appropriate unevenness on the surface of the raw material coal powder, and makes it easier to introduce a surface structure suitable for rapid charging onto the particle surfaces after graphitization. On the other hand, if the aromatic index fa is too small, the unevenness caused by the pulverization after the heat treatment of the raw coal composition tends to grow larger, and even after graphitization, the atoms on the outermost surface of the particles are unlikely to rearrange into a surface superstructure suitable for rapid charging, which is undesirable.
[0029] In addition, it is preferable that the aromatic index fa is 0.65 or less, since the bulk mesophase can be more easily restricted to a small size by the gas generated during the coking treatment. On the other hand, if the aromatic index fa is too large, a large number of mesophases are rapidly generated in the matrix during the coking process, and the rate at which the mesophases coalesce is faster than the rate at which the mesophases grow as a single unit. As a result, it becomes difficult to obtain the effect of reducing the size of the bulk mesophase by the gas generated during the coking process, and it becomes difficult to restrict the size of the bulk mesophase to a small size, which is undesirable.
[0030] In view of the above, the raw oil composition in step A has a normal paraffin content of preferably 5 to 20 mass%, and more preferably 10 to 15 mass%, based on the total amount of the raw oil composition, and has an aromatic index fa determined by the Knight method of preferably 0.3 to 0.65, and more preferably 0.35 to 0.60, and even more preferably 0.40 to 0.55. In addition, the feed oil composition in step A is preferably a heavy oil having a normal paraffin content and an aromatics index fa within the above-mentioned ranges and having been subjected to advanced hydrodesulfurization treatment.
[0031] The feed oil composition in step A has a normal paraffin content and an aromatics index fa within the above ranges, and a density D of 0.91 to 1.02 g / cm 3 In addition, the viscosity V is preferably 10 to 220 mm 2 It is more preferred that the .alpha. / s.
[0032] <Caulking treatment> As a method for coking the raw oil composition by the delayed coking process in step A, for example, a known method described in Japanese Patent No. 5415684 can be used. The method for coking the raw oil composition by the delayed coking process is very suitable for mass production of raw materials for high-quality artificial graphite materials.
[0033] In step A, a delayed coking process is used as a method for coking the raw oil composition. The coking process causes thermal decomposition and polycondensation reactions of the raw oil composition, and a raw coal composition is obtained through a process in which large liquid crystals called mesophase are generated as an intermediate product.
[0034] As for the conditions of the delayed coker, for example, the pressure is preferably 0.1 to 0.8 MPa, and more preferably 0.2 to 0.6 MPa. The temperature is preferably from 400 to 600°C, and more preferably from 490 to 540°C.
[0035] In the production method of this embodiment, the size of the carbon hexagonal network plane constituting the mesophase is controlled by the gas generated from the feedstock oil composition during the coking treatment. Therefore, the residence time of the gas generated from the feedstock oil composition during the coking treatment in the system is an important control parameter for determining the size of the carbon hexagonal network plane. The residence time of the gas generated during the coking treatment in the system can be adjusted by the pressure during the coking treatment. Therefore, when the pressure in the coking treatment is within the above-mentioned preferred range, it becomes easier to limit the rate at which the gas generated from the stock oil composition is released outside the system. Furthermore, when the temperature in the coking treatment is within the above-mentioned preferred range, a better mesophase can be grown from the feed oil composition adjusted to obtain the effects of the present invention.
[0036] On the other hand, if the temperature in the coking treatment is too low and the pressure is too high, the amount of gas generated during the coking treatment becomes insufficient, and the crystal structure of the raw coke composition grows too much. In this case, it is difficult to form pores having openings on the particle surfaces of the heat-treated raw coke composition prepared by the heat treatment in step B described below, and unevenness on the particle surfaces, which is undesirable. Furthermore, if the temperature in the coking treatment is too high and the pressure is too low, an excessive amount of gas is generated during the coking treatment, and even if the material is heat-treated in the subsequent graphitization step, the graphite crystal structure is unlikely to grow, and high capacity is not achieved, making the material unsuitable as an artificial graphite material for the negative electrode of a lithium-ion secondary battery.
[0037] The raw coal composition in step A is a composition containing raw coke.
[0038] <About Process B> Step B is a step of heat-treating the above-mentioned raw coke composition to obtain a heat-treated raw coke composition. The heat treatment in step B is carried out in an atmosphere of an inert gas such as nitrogen, argon, or helium. In this case, the atmospheric gas may contain oxygen gas in a range of 0.01 to 21% by volume with respect to the total amount of the atmospheric gas. Examples of the heat treatment include a method in which the raw coke composition is placed in a sagger and a roller hearth kiln is used, and a method in which the raw coke composition is directly placed in a rotary kiln.
[0039] In the manufacturing method of the artificial graphite material for lithium ion secondary battery negative electrodes of this embodiment, the volatile content and true density of the raw coal powder are correlated with the heat treatment temperature (maximum temperature reached) and heat treatment time (time for which the maximum temperature is held) of the raw coal composition. As a general trend, the higher the heat treatment temperature or the longer the heat treatment time, the lower the volatile content of the heat-treated raw coal composition and the raw coal powder obtained therefrom, and the higher the true density. The heat treatment temperature and heat treatment time of the raw coal composition are such that the volatile content of the raw coal powder is less than 3.71% and the true density of the raw coal powder is 1.22 g / cm 3 Super 1.73g / cm 3 It must be set to be less than
[0040] The lower limit of the maximum temperature reached in step B is preferably 450°C or higher, more preferably 500°C or higher, and even more preferably 550°C or higher, because this makes it easier to adjust the volatile content and true density of the raw coal powder within the above ranges, and also enables the heat treatment time to be shortened, thereby further reducing production costs. The upper limit of the maximum attainable temperature in step B is preferably 750°C or less, more preferably 700°C or less, and even more preferably 650°C or less, because this makes it easier to adjust the volatile content and true density of the raw coal powder within the above ranges and further improves the quality stability of the heat-treated raw coal composition and raw coal powder.
[0041] For example, the maximum temperature reached in step B is preferably 450 to 750°C, more preferably 500 to 700°C, and further preferably 550 to 650°C.
[0042] If the heat treatment temperature is too low, it takes a long time and the production cost increases unnecessarily, which is not preferable, whereas if the heat treatment temperature is too high, the properties (volatile matter and true density) of the heat-treated raw coal composition and the raw coal powder vary widely, which is not preferable from the viewpoint of quality stability.
[0043] The lower limit of the holding time of the maximum temperature achieved in step B is preferably 0.1 hour or more, more preferably 0.2 hour or more, and even more preferably 0.5 hour or more, because this makes it easy to adjust the volatile content and true density of the raw coal powder to within the above ranges and improves the quality stability of the heat-treated raw coal composition and raw coal powder. The upper limit of the holding time of the maximum temperature in step B is preferably 3 hours or less, more preferably 2 hours or less, and even more preferably 1 hour or less, because this makes it easier to adjust the volatile content and true density of the raw coal powder within the above ranges and also makes it possible to further reduce production costs.
[0044] For example, the holding time at the maximum temperature in step B is preferably 0.1 to 3 hours, more preferably 0.2 to 2 hours, and further preferably 0.5 to 1 hour.
[0045] <About Process C> Step C is a step of pulverizing the above-mentioned heat-treated raw coke composition to obtain raw coke powder. The raw coal powder obtained by step C has a volatile content of less than 3.71% and a true density of 1.22 g / cm 3 Super 1.73g / cm 3 is less than. As described above, the volatile content and true density of the raw coal powder are controlled by step B, and are little affected by the crushing conditions in step C.
[0046] In this specification, the term "volatile matter" refers to the volatile matter [mass fraction (%)] calculated in accordance with "7. Volatile matter determination method" in "7.2 Vertical tubular electric furnace method" and "b) In the case of coke" described in "Coals and cokes - Proximate analysis methods" of JIS M 8812 (2004).
[0047] In this specification, the term "true density" refers to the true density [g / cm3] calculated in accordance with "7.3 True density test method" in "7. Density and porosity test method" described in "Cokes - Test methods" of JIS K 2151 (2004). 3 ] means.
[0048] The true density of the raw coal composition produced by subjecting the raw oil composition to a delayed coking process is usually 1.1 to 1.4 g / cm 3 and the volatile content is usually 5 to 15% (see, for example, "Fuel Association Journal," Vol. 58, No. 642 (1979), pp. 257-263). Typical changes that occur when a raw coke composition with such properties is heat treated are a decrease in the volatile content and an increase in the true density. The reason for the decrease in the volatile content is that the volatile content contained in the raw coke composition is a reaction product of the raw oil composition that remains in a state where the thermal decomposition and polycondensation reaction are insufficient in the delayed coking process, and therefore dissipates during the subsequent heat treatment. The reason for the increase in true density is that the thermal decomposition and polycondensation reaction proceed further by the heat treatment. The raw coal composition having such characteristics is heat-treated and then pulverized to obtain a raw coal powder having a volatile content of less than 3.71% and a true density of 1.22 g / cm. 3 Super 1.73g / cm 3 If the temperature is controlled to less than 100° C., a surface superstructure having an appropriate structure is formed such that even if a rapid intercalation reaction of lithium ions occurs (even if rapid charging is performed), electrodeposition of lithium metal does not occur. Therefore, the artificial graphite material for the negative electrode of a lithium ion secondary battery obtained thereafter can be suitably suppressed from deteriorating in discharge capacity even if rapid charging is repeated as the charging method.
[0049] Here, the "surface superstructure" refers to a structure in which the carbon atoms on the outermost surface of the raw coal powder particles are arranged in an orderly manner with a different regularity from that in the interior of the particles. The surface superstructure formed on the outermost surface of the raw coal powder particles will be described in more detail by taking as an example the surface superstructure formed on the outermost surface of the raw coal powder particles. The outermost surface atoms present on the fracture surface generated by the pulverization of the heat-treated raw coal composition have no atoms to bond with on one side, so there are excess bonds. If these excess bonds (dangling bonds) are present at a high density, the surface state becomes unstable, so the atoms on the outermost surface rearrange themselves in the subsequent heat treatment, and rearrange so as to reduce the number of dangling bonds as much as possible. The rearrangement does not occur randomly, but occurs regularly, so that the atoms on the outermost surface are arranged in an orderly manner with regularity. This regularity is different from that in the interior. This special atomic arrangement that appears only on the surface is called the surface superstructure.
[0050] Since the volatile content of the raw coal powder is less than 3.71%, the surface and internal bulk of the raw coal powder form volatile evaporation paths, i.e., pores of various sizes, large and small, in a tortuous shape. In addition, due to the mechanical energy caused by crushing, small pores grow as cavities (cracks), and large pores grow as cavities and are then cut (crushed). As a result, the raw coal powder has pores with openings on the particle surface and unevenness on the particle surface.
[0051] The raw coal powder obtained in step C has a volatile content of less than 3.71%, preferably 0.1% or more and 3.6% or less. In addition, the raw coal powder has a true density of 1.22 g / cm 3 Super 1.73g / cm 3 and preferably less than 1.26 g / cm 3 More than 1.68g / cm 3 The following is the result.
[0052] If the heat treatment reaction of the raw coke composition proceeds too far, for example, the volatile content of the raw coke powder is less than 0.1% and the true density is 1.68 g / cm 3 If the specific surface area is larger than this, the growth of the hexagonal network planes composed of carbon atoms becomes too large, making it difficult to form raw coal powder with a large specific surface area. Therefore, the discharge capacity of the artificial graphite material obtained thereafter may be significantly degraded when rapid charging is repeated.
[0053] Conversely, when the heat treatment of the raw coal composition is insufficient, for example, the volatile content of the raw coal powder is more than 3.6% and the true density is 1.26 g / cm 3 If the delayed coking time is less than 10 minutes, only compounds with relatively low molecular weights that have not undergone the thermal decomposition or polycondensation reactions in the delayed coking process will evaporate, and the particle surfaces of the raw coal powder will not be unevenly sized after subsequent crushing, making it difficult to form raw coal powder with a large specific surface area. As a result, there is a risk that the discharge capacity will be significantly degraded when rapid charging is repeated. For the above reasons, it is preferable that the volatile matter content of the raw coal powder is 0.1 to 3.6%, and the true density is 1.26 to 1.68 g / cm. 3 It is preferable that:
[0054] The pulverization means in step C may be any known method, such as a method using a hammer mill or a method using an airflow jet mill, and is not particularly limited.
[0055] The average particle size of the raw coal powder obtained in step C is appropriately adjusted so that the average particle size of the artificial graphite material for lithium ion secondary battery negative electrodes obtained in step D described below is less than 12.6 μm. The average particle size of the raw coal powder is preferably less than 12.6 μm, more preferably 1 μm or more and 12.5 μm or less, even more preferably 2 μm or more and 12 μm or less, particularly preferably 3.1 μm or more and 11.8 μm or less, and most preferably 3.1 μm or more and 9 μm or less.
[0056] In this specification, the term "average particle size" refers to a value calculated from the particle size distribution measurement results obtained by measuring the particle size distribution using a laser diffraction / scattering type particle size distribution analyzer in accordance with "weighted volume-based average diameter" in "4.2.3 Weighted average particle size" of "Expression of particle size measurement results - Part 2: Calculation of average particle size or average particle diameter and moment from particle size distribution" of JIS Z 8819-2 (2001).
[0057] The pulverization conditions in step C are appropriately set so that the raw coal powder has an average particle size of less than 12.6 μm.
[0058] The raw coal powder obtained in step C may be classified to have a predetermined particle size. The classification means in step C may be a known method such as a method using a classifier, and is not particularly limited.
[0059] <About Process D> Step D is a step of graphitizing the raw coal powder described above to obtain an artificial graphite material for a lithium ion secondary battery negative electrode. Specifically, the raw coal powder is further heat-treated to remove volatile components from the raw coal powder, dehydrated, pyrolyzed, and subjected to a solid-phase graphitization reaction. By carrying out this graphitization treatment, an artificial graphite material for the negative electrode of a lithium-ion secondary battery with stable quality can be obtained.
[0060] The artificial graphite material for a lithium ion secondary battery negative electrode obtained by step D has an average particle size of less than 12.6 μm as measured by a laser diffraction particle size distribution measuring device. The average particle size of the artificial graphite material for lithium ion secondary battery negative electrodes is less than 12.6 μm, preferably 1 μm or more and 12.5 μm or less, more preferably 2 μm or more and 12 μm or less, even more preferably 3.1 μm or more and 11.8 μm or less, and particularly preferably 3.1 μm or more and 9 μm or less.
[0061] If the upper limit of the average particle size of the artificial graphite material for the negative electrode of a lithium ion secondary battery is 12.6 μm or more, this is not preferable because the discharge capacity decreases significantly due to repeated rapid charging. The lower limit of the average particle size of the artificial graphite material for lithium ion secondary battery negative electrodes is not particularly limited, but from the viewpoint of production efficiency, it is preferably 1 μm or more, more preferably 2 μm or more, and even more preferably 3.1 μm or more.
[0062] When the average particle size of the artificial graphite material for the negative electrode of a lithium ion secondary battery is within the above preferred range, the discharge capacity is less likely to deteriorate even when charge / discharge cycles are repeated at a large current, and the production efficiency is also improved.
[0063] Examples of graphitization methods include a heat treatment in which volatile components are removed from raw coal powder, calcination is performed to obtain calcined coke, a carbonization treatment is performed to carbonize the coke, and then a graphitization treatment is performed. The calcination and carbonization treatment may or may not be carried out as required. In the graphitization method, even if the calcination and carbonization processes are omitted, there is almost no effect on the physical properties of the final artificial graphite material produced.
[0064] The calcination may be performed, for example, by a method in which a heat treatment is performed in an inert gas atmosphere such as nitrogen, argon, or helium at a maximum temperature of preferably 500 to 1500° C., more preferably 900 to 1200° C., for a holding time at the maximum temperature of 0 to 10 hours.
[0065] The carbonization treatment may be carried out, for example, in an inert gas atmosphere such as nitrogen, argon, or helium at a maximum temperature of preferably 500 to 1500° C., more preferably 900 to 1500° C., for a holding time of the maximum temperature of 0 to 10 hours.
[0066] The graphitization treatment may be carried out, for example, in an inert gas atmosphere such as nitrogen, argon, or helium, at a maximum temperature of preferably 2500 to 3200°C, more preferably 2800 to 3200°C, for a holding time at the maximum temperature of 0 to 100 hours. The graphitization treatment may be carried out, for example, by sealing the raw coal powder in a crucible made of graphite and using a graphitization furnace such as an Acheson furnace or an LWG furnace.
[0067] The method for producing an artificial graphite material for a lithium ion secondary battery negative electrode according to this embodiment includes the steps A to D described above. In the method for producing an artificial graphite material for a lithium ion secondary battery negative electrode of this embodiment, the volatile content of the raw coal powder obtained by step C is 0.1% or more and 3.6% or less, and the true density of the raw coal powder is 1.26 g / cm 3 More than 1.68g / cm 3 In other words, the specific surface area of the raw coal powder is controlled to be larger. Furthermore, the average particle size of the artificial graphite material for the negative electrode of a lithium ion secondary battery is controlled to be less than 12.6 μm. By controlling the specific surface area and average particle size of artificial graphite material for the negative electrode of lithium-ion secondary batteries, it is possible to form a surface superstructure with an appropriate structure on the particle surface. As a result, even if a rapid intercalation reaction of lithium ions occurs (even when rapid charging is performed), electrodeposition of lithium metal is unlikely to occur, and deterioration of the discharge capacity is suitably suppressed even when rapid charging is performed repeatedly as a charging method. Therefore, a lithium ion secondary battery having a negative electrode containing the artificial graphite material obtained by the method for producing an artificial graphite material for a lithium ion secondary battery negative electrode of this embodiment is less likely to experience deterioration in discharge capacity even when subjected to repeated rapid charging.
[0068] (Artificial graphite material for negative electrodes of lithium-ion secondary batteries) The artificial graphite material for lithium ion secondary battery negative electrodes of this embodiment is an artificial graphite material for lithium ion secondary battery negative electrodes obtained by the above-mentioned method for producing an artificial graphite material for lithium ion secondary battery negative electrodes.
[0069] In the artificial graphite material for lithium ion secondary battery negative electrodes of this embodiment, the specific surface area of the raw material coal powder used as the raw material is controlled to be larger, and the average particle size of the artificial graphite material for lithium ion secondary battery negative electrodes is less than 12.6 μm. Therefore, in the artificial graphite material for lithium ion secondary battery negative electrodes finally obtained in this embodiment, lithium ions can diffuse at high speed inside the particles of the artificial graphite material, so that the artificial graphite material is useful as a material for lithium ion secondary battery negative electrodes.
[0070] (Anode for lithium-ion secondary batteries) The negative electrode for a lithium ion secondary battery of this embodiment contains the artificial graphite material for a lithium ion secondary battery negative electrode of the above-mentioned embodiment. Specifically, the material contains the artificial graphite material for a lithium ion secondary battery negative electrode, a binder, and a conductive assistant which is optionally contained.
[0071] <Graphite materials> The negative electrode for a lithium ion secondary battery of this embodiment may contain, as a graphite material, not only the artificial graphite material for a lithium ion secondary battery negative electrode of the above-mentioned embodiment, but also one or more types of known graphite materials or amorphous carbon materials, as necessary.
[0072] Examples of known graphite materials include artificial graphite materials other than the artificial graphite material for the lithium ion secondary battery negative electrode of the above-mentioned embodiment (hereinafter referred to as "other artificial graphite materials"), natural graphite-based materials, etc. Also, examples of amorphous carbon materials include well-known graphitizable carbon materials and non-graphitizable carbon materials.
[0073] Examples of natural graphite-based materials include graphite-like materials produced in nature, the graphite-like materials that have been highly purified and then made into spheres (including mechanochemical treatments), high-purity products or spheres whose surfaces are coated with another type of carbon (for example, pitch-coated products, CVD-coated products, etc.), and products that have been plasma-treated.
[0074] The shapes of other artificial graphite materials, natural graphite-based materials, and amorphous carbon materials are not particularly limited, and may be, for example, flake-like, spherical, or lumpy.
[0075] When the carbon material contains other artificial graphite materials, the mixing ratio of the artificial graphite material for lithium ion secondary battery negative electrodes of the above-mentioned embodiments and the other artificial graphite materials can be any ratio. For example, in a 100% mixture of the artificial graphite material for a lithium ion secondary battery negative electrode of the above-mentioned embodiment and another artificial graphite material, the artificial graphite material for a lithium ion secondary battery negative electrode of the above-mentioned embodiment is preferably contained in an amount of 20% by mass or more, more preferably 30% by mass or more, and even more preferably 50% by mass or more.
[0076] <Binder> As the binder, any known binder that is used in negative electrodes for lithium ion secondary batteries can be used. For example, carboxymethyl cellulose (CMC), polyvinylidene fluoride, polytetrafluoroethylene, SBR (styrene-butadiene rubber), etc. can be used alone or in combination of two or more. The content of the binder in the negative electrode for a lithium ion secondary battery of this embodiment may be appropriately set as necessary in terms of designing the lithium ion secondary battery, and is preferably, for example, 1 to 30 parts by mass per 100 parts by mass of the above-mentioned graphite material.
[0077] <Conductive assistant> As the conductive assistant, any known material used in the negative electrode of a lithium ion secondary battery can be used. For example, carbon black, graphite, acetylene black, conductive indium-tin oxide, conductive polymers such as polyaniline, polythiophene, polyphenylene vinylene, etc. can be used alone or in combination of two or more kinds. The content of the conductive assistant in the negative electrode for a lithium ion secondary battery of this embodiment may be appropriately set as necessary in terms of designing the lithium ion secondary battery, and is preferably, for example, 1 to 15 parts by mass per 100 parts by mass of the above-mentioned graphite material.
[0078] As a method for producing the negative electrode for a lithium ion secondary battery of this embodiment, for example, the negative electrode can be produced by producing a negative electrode mixture which is a mixture containing a graphite material including the artificial graphite material for a lithium ion secondary battery negative electrode of the above-mentioned embodiment, a binder, a conductive assistant which is contained as necessary, and a solvent, and then pressure-molding the negative electrode mixture into a predetermined dimension.
[0079] <Solvent> As the solvent used in the negative electrode mixture, a known solvent used in the negative electrode for lithium ion secondary batteries can be used. For example, organic solvents such as dimethylformamide, N-methylpyrrolidone, isopropanol, toluene, and the like, water, and the like can be used alone or in combination of two or more kinds.
[0080] As a means for mixing the graphite material, the binder, the conductive assistant that is contained as necessary, and the solvent, for example, a known device such as a screw type kneader, a ribbon mixer, a universal mixer, or a planetary mixer can be used.
[0081] The electrode mixture can be pressure-molded to a predetermined size by using, for example, roll pressure or press pressure. The negative electrode mixture is preferably pressure-molded at a pressure of about 100 to 300 MPa.
[0082] The negative electrode for lithium ion secondary batteries of this embodiment may be manufactured, for example, by the method shown below. That is, a graphite material containing the artificial graphite material for lithium ion secondary battery negative electrodes of the above-mentioned embodiment, a binder, a conductive assistant contained as necessary, and a solvent are kneaded by a known method to manufacture a slurry or paste-like negative electrode mixture. Then, the slurry or paste-like negative electrode mixture is applied to a negative electrode current collector such as copper foil, and dried to form a sheet or pellet-like shape, etc., to form a layer made of the dried negative electrode mixture. Then, the layer made of the dried negative electrode mixture is rolled and cut to a predetermined size to manufacture a negative electrode for lithium ion secondary batteries.
[0083] The method for applying the negative electrode mixture in a slurry or paste form onto the negative electrode current collector is not particularly limited. For example, known methods such as metal mask printing, electrostatic painting, dip coating, spray coating, roll coating, doctor blade method, gravure coating, screen printing, and die coater method can be used.
[0084] The layer made of the dried negative electrode mixture can be rolled using, for example, a flat press, a calendar roll, etc. The layer made of the dried negative electrode mixture formed on the negative electrode current collector can be integrated with the negative electrode current collector by a known method such as a method using a roll, a press, or a combination of these.
[0085] There are no particular limitations on the material of the negative electrode current collector, so long as it does not form an alloy with lithium. Specific examples of the material of the negative electrode current collector include copper, nickel, titanium, and stainless steel. The shape of the negative electrode current collector is not particularly limited and may be any shape. Specifically, the shape of the negative electrode current collector may be a foil, a perforated foil, a mesh, or the like, and may be a band-like shape as a whole.
[0086] As the negative electrode current collector, for example, a porous material such as porous metal (foamed metal) or carbon paper may be used.
[0087] The negative electrode for a lithium ion secondary battery of this embodiment described above contains the artificial graphite material for a lithium ion secondary battery negative electrode of the above-mentioned embodiment, and therefore the discharge capacity is unlikely to deteriorate even when charge / discharge cycles are repeated at a large current.
[0088] (Lithium-ion secondary battery) The lithium ion secondary battery of this embodiment is a lithium ion secondary battery having the negative electrode for lithium ion secondary batteries of the above-mentioned embodiment. An embodiment of the lithium ion secondary battery of the present invention will be described with reference to FIG. FIG. 1 is a schematic cross-sectional view showing an example of the lithium ion secondary battery of the present embodiment. A lithium ion secondary battery 10 shown in FIG. 1 has a negative electrode 11 integrated with a negative electrode current collector 12, and a positive electrode 13 integrated with a positive electrode current collector 14. In the lithium ion secondary battery 10, the negative electrode for lithium ion secondary batteries of the present embodiment described above is used as the negative electrode 11. The negative electrode 11 and the positive electrode 13 are disposed opposite each other with a separator 15 interposed therebetween. The negative electrode 11 integrated with the negative electrode current collector 12 and the positive electrode 13 integrated with the positive electrode current collector 14 are covered with an aluminum laminate exterior 16 . An electrolyte is injected into the aluminum laminate exterior 16 .
[0089] The positive electrode 13 contains an active material, a binder, and a conductive assistant that is contained as necessary. As the active material, a known material used in a positive electrode for a lithium ion secondary battery can be used, and a metal compound, a metal oxide, a metal sulfide, or a conductive polymer material capable of doping or intercalating lithium ions can be used. Specifically, the active material can be lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMn2O4), and a composite oxide (LiCo X Ni Y Mn ZO2, X+Y+Z=1), lithium vanadium compounds, V2O5, V6O 13 , VO2, MnO2, TiO2, MoV2O8, TiS2, V2S5, VS2, MoS2, MoS3, Cr3O8, Cr2O5, olivine-type LiMPO4 (M: Co, Ni, Mn, Fe), conductive polymers such as polyacetylene, polyaniline, polypyrrole, polythiophene, polyacene, porous carbon, and mixtures thereof.
[0090] As the binder, the same binder as that used in the negative electrode 11 described above can be used. As the conductive assistant, the same conductive assistant as that used in the negative electrode 11 described above can be used. For example, a valve metal or an alloy thereof that forms a passive film on the surface by anodization in an electrolyte is preferably used as the positive electrode current collector 14. Specifically, Al, Ti, Zr, Hf, Nb, Ta, and alloys containing these metals can be used. In particular, Al and its alloys are preferred because they are lightweight and have a high energy density.
[0091] For example, a nonwoven fabric, a cloth, a microporous film, or a combination thereof, mainly composed of a polyolefin such as polyethylene or polypropylene, can be used as the separator 15. If the lithium ion secondary battery has a structure in which the positive electrode and the negative electrode are not in direct contact with each other, a separator is not necessary.
[0092] Known organic electrolytic solutions, inorganic solid electrolytes, and polymer solid electrolytes used in lithium ion secondary batteries can be used as the electrolytic solution and electrolyte used in the lithium ion secondary battery 10. From the viewpoint of electrical conductivity, it is preferable to use an organic electrolytic solution as the electrolytic solution.
[0093] Examples of the organic electrolyte include ethers such as dibutyl ether, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, and ethylene glycol phenyl ether; amides such as N-methylformamide, N,N-dimethylformamide, N-ethylformamide, N,N-diethylformamide, N-methylacetamide, N,N-dimethylacetamide, N-ethylacetamide, and N,N-diethylacetamide; sulfur-containing compounds such as dimethylsulfoxide and sulfolane; methyl ethyl ketone, methyl isobutyl ketone, and the like. Examples of the organic electrolyte include dialkyl ketones such as tetrahydrofuran and 2-methoxytetrahydrofuran, cyclic ethers such as ethylene carbonate, butylene carbonate, propylene carbonate, and vinylene carbonate, chain carbonates such as diethyl carbonate, dimethyl carbonate, methyl ethyl carbonate, and methyl propyl carbonate, cyclic carbonates such as γ-butyrolactone and γ-valerolactone, chain carbonates such as methyl acetate, ethyl acetate, methyl propionate, and ethyl propionate, and organic solvents such as N-methyl 2-pyrrolidinone, acetonitrile, and nitromethane. These organic electrolytes can be used alone or in combination of two or more.
[0094] As the electrolyte, various known lithium salts can be used, such as LiClO4, LiBF4, LiPF6, LiAlCl4, LiSbF6, LiSCN, LiCl, LiCF3SO3, LiCF3CO2, LiN(CF3SO2)2, and LiN(C2F5SO2)2.
[0095] Examples of the polymer solid electrolyte include polyethylene oxide derivatives and polymers containing said derivatives, polypropylene oxide derivatives and polymers containing said derivatives, phosphate polymers, polycarbonate derivatives and polymers containing said derivatives, and the like.
[0096] The lithium ion secondary battery 10 of this embodiment includes the negative electrode 11 containing the artificial graphite material for lithium ion secondary battery negative electrodes of this embodiment described above, and therefore the discharge capacity is unlikely to deteriorate even when the charge / discharge cycle is repeated at a large current. Therefore, the lithium ion secondary battery 10 of this embodiment can be preferably used for automobiles such as hybrid automobiles, plug-in hybrid automobiles, and electric automobiles, and for industrial purposes such as power storage in system infrastructure.
[0097] The lithium ion secondary battery of this embodiment may be any battery that uses the negative electrode for lithium ion secondary batteries of the above-described embodiment, and is not subject to any restrictions on the selection of components necessary for the battery configuration other than the negative electrode.
[0098] Specifically, the structure of the lithium ion secondary battery of the present invention is not limited to the lithium ion secondary battery 10 shown in FIG.
[0099] The method for producing the lithium ion secondary battery of this embodiment is not particularly limited as long as it utilizes the negative electrode for lithium ion secondary batteries of the above-mentioned embodiment, and any known production method can be used. For example, the method includes a step of arranging the negative electrode for lithium ion secondary battery of the above embodiment and a positive electrode with a separator interposed therebetween. More specifically, it is preferable to include a step of integrating the negative electrode for lithium ion secondary battery of the above embodiment with a negative electrode current collector, integrating a positive electrode with a positive electrode current collector, and arranging the negative electrode integrated with the negative electrode current collector and the positive electrode integrated with the positive electrode current collector with a separator interposed therebetween. Next, a single-layer electrode body in which a negative electrode integrated with a negative electrode current collector and a positive electrode integrated with a positive electrode current collector are arranged opposite each other via a separator is housed in an outer casing, and an electrolyte is injected into the inside of the outer casing to obtain the lithium-ion secondary battery of this embodiment.
[0100] The lithium ion secondary battery may have a structure in which, for example, a wound electrode group in which a strip-shaped positive electrode and a negative electrode are spirally wound with a separator interposed therebetween is inserted into a battery case and sealed. Alternatively, the lithium ion secondary battery may have a structure in which a stacked electrode group in which a flat-shaped positive electrode and a negative electrode are sequentially stacked with a separator interposed therebetween is enclosed in an exterior body.
[0101] The lithium ion secondary battery of this embodiment can be used as, for example, a paper type battery, a button type battery, a coin type battery, a laminated type battery, a cylindrical type battery, a prismatic battery, or the like. EXAMPLES
[0102] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples. In this example, the raw material oil composition used in the production of the artificial graphite material for the negative electrode of a lithium ion secondary battery in Example 1 is referred to as the "raw material oil composition of Example 1", and other raw materials and manufactured products are also referred to in the same manner.
[0103] <Production of artificial graphite material for negative electrodes of lithium-ion secondary batteries> Example 1 <Production of raw material oil composition> Atmospheric distillation residual oil is distilled under reduced pressure and then hydrodesulfurized (sulfur content 380 ppm by mass, density at 15°C 0.83 g / cm 3 ) was subjected to fluid catalytic cracking at a reaction temperature of 530°C, total pressure of 0.23MPa, catalyst / oil ratio of 13, and contact time of 7 seconds to obtain fluid catalytic cracking residue. The catalyst used was a platinum-supported silica-alumina catalyst. The "sulfur content" refers to the value measured according to JIS K2541.
[0104] The fluid catalytic cracking residual oil thus obtained was mixed with an equal volume of n-heptane, and then selectively extracted with dimethylformamide to separate it into aromatic and saturated fractions.
[0105] Furthermore, atmospheric distillation residual oil (sulfur content 0.35 mass%, density at 15 °C 0.92 g / cm3 ) was distilled under reduced pressure at a furnace outlet temperature of 350°C and a pressure of 1.3 kPa to obtain a vacuum distillation residual oil with an initial boiling point of 410°C, an asphalt content of 9 mass%, a saturates content of 61 mass%, a sulfur content of 0.1 mass%, and a nitrogen content of 0.3 mass%. The vacuum distillation residual oil was mixed with an equal volume of n-heptane, and then selectively extracted with dimethylformamide to separate it into aromatic and saturated fractions. The "nitrogen content" refers to a value measured according to JIS K2609. The "saturated content" and "asphalt content" refer to values measured using a thin layer chromatograph.
[0106] The fluid catalytic cracking residual oil thus obtained, the saturated fraction of the fluid catalytic cracking residual oil, and the saturated fraction of the vacuum distillation residual oil were mixed in a mass ratio of 43:50:7 to obtain the stock oil composition of Example 1. The normal paraffin content and aromatic index fa of the obtained stock oil composition of Example 1 were determined by the methods described below. The results are shown in Table 1.
[0107] [Normal paraffin content] The normal paraffin content of the feedstock oil composition was measured by a gas chromatograph equipped with a capillary column. Specifically, after calibration with a standard normal paraffin, a sample of non-aromatic components separated by elution chromatography was passed through the capillary column and measured. From this measurement, the content (mass%) based on the total mass of the feedstock oil composition was calculated.
[0108] [Aromatic index fa] The aromatic index fa of the feedstock oil composition was calculated by the Knight method. 13 The spectrum of aromatic carbon by C-NMR was divided into three components (A1, A2, A3). Here, A1 is the number of carbon atoms in the aromatic ring (the number of substituted aromatic carbons and half of the unsubstituted aromatic carbons ( 13 C-NMR peak of about 40-60 ppm), and A2 is the remaining half of the unsubstituted aromatic carbon ( 13 C-NMR peak of about 60 to 80 ppm), and A3 is the number of aliphatic carbon atoms ( 13(This corresponds to a peak at about 130 to 190 ppm in C-NMR.) The aromatic index fa was calculated using A1, A2, and A3 as fa = (A1 + A2) / (A1 + A2 + A3).
[0109] ≪Process A≫ Next, the raw oil composition of Example 1 was placed in a test tube and subjected to a heat treatment at normal pressure and 500° C. for 3 hours as a coking treatment to convert it into coke, thereby obtaining a raw coal composition of Example 1.
[0110] ≪Process B≫ The obtained raw coke composition of Example 1 was heated to 550°C under a mixed gas flow with a nitrogen / oxygen volume ratio of 83:17 to obtain a heat-treated raw coke composition of Example 1. The heat treatment method was such that the temperature was increased from room temperature (25°C) to 550°C for 1 hour, held at 550°C for 1 hour, and decreased from 550°C to 400°C for 1 hour, and after 400°C, the mixture was allowed to cool for 4 hours while continuing to flow through the mixed gas.
[0111] ≪Process C≫ The obtained heat-treated raw coal composition of Example 1 was pulverized in an air-flow jet mill so that the average particle size determined by the method described below was in the range of 7.5 to 8.5 μm, to obtain the raw coal powder of Example 1. In addition, the volatile content and true density of the raw coal powder were determined by the methods described below. The results are shown in Table 1.
[0112] [Measurement of average particle size] The average particle size was measured using a laser diffraction / scattering particle size distribution analyzer MT3300EXII manufactured by Microtrack Bell Co., Ltd. The dispersion liquid used for the measurement was prepared by thoroughly mixing approximately 0.5 g of graphite powder with a 0.1 wt% aqueous solution of sodium hexametaphosphate (several drops) and a surfactant (several drops) in a mortar until homogeneous, then adding 40 mL of an aqueous solution of 0.1 wt% sodium hexametaphosphate and dispersing with an ultrasonic homogenizer. The particle size distribution measurement results obtained were calculated in accordance with "weighted volume-based mean diameter" in "4.2.3 Weighted mean particle diameter" of "Expression of particle size measurement results - Part 2: Calculation of mean particle size or mean particle diameter and moment from particle size distribution" of JIS Z 8819-2 (2001).
[0113] [Measurement of volatile matter] The volatile matter [mass fraction (%)] of the raw coal powder was determined in accordance with "7. Volatile matter determination method" in "7.2 Vertical tubular electric furnace method" and "b) In the case of coke" in "Coals and cokes - Methods of proximate analysis" of JIS M 8812 (2004).
[0114] [True density measurement] True density of raw coal powder [g / cm 3 ] was determined in accordance with "7.3 True density test method" in "7. Density and porosity test method" in "Cokes - Test methods" of JIS K 2151 (2004).
[0115] ≪Process D≫ The raw coal powder of Example 1 was placed in a crucible made of graphite, and the crucible was embedded in packing coke, which serves as a heating and heat-insulating material in an Acheson furnace, and then graphitized at 2950°C. The graphitization treatment consisted of heating the material from room temperature (25°C) to 2950°C for 130 hours, holding the material at 2950°C for 8 hours, and then leaving the material to cool for 25 days before removing it from the container to obtain the artificial graphite material for the negative electrode of a lithium ion secondary battery of Example 1. The average particle size of the artificial graphite material for the negative electrode of a lithium ion secondary battery of Example 1 was calculated by the method described in [Measurement of average particle size] above. The results are shown in Table 1.
[0116] Example 2 <Production of raw material oil composition> Atmospheric distillation residual oil with a sulfur content of 3.1% by mass was hydrodesulfurized in the presence of a catalyst so that the hydrocracking rate was 25% or less to obtain a hydrodesulfurized oil. The hydrodesulfurization conditions were a total pressure of 18 MPa, a hydrogen partial pressure of 16 MPa, and a temperature of 380°C.
[0117] The hydrodesulfurized oil thus obtained and the fluid catalytic cracking residual oil obtained in Example 1 were mixed in a mass ratio of 5:95 to obtain a stock oil composition of Example 2. The normal paraffin content and aromatics index fa of the base oil composition of Example 2 were determined by the same methods as in Example 1. The results are shown in Table 1.
[0118] ≪Process A≫ The raw oil composition of Example 2 was coked by the same coking treatment as in Example 1 to obtain a raw coal composition of Example 2.
[0119] ≪Process B≫ The raw coke composition of Example 2 was heated at 700° C. in a mixed gas flow having a nitrogen / oxygen volume ratio of 98:2 to obtain a heat-treated raw coke composition of Example 2. The heat treatment method was as follows: the temperature was increased from room temperature (25°C) to 700°C for 2 hours, held at 700°C for 1 hour, and decreased from 700°C to 400°C for 2 hours. After 400°C, the material was allowed to cool for 4 hours while continuing the flow of the mixed gas.
[0120] ≪Process C≫ The heat-treated raw coal composition of Example 2 was pulverized in an air jet mill so that the average particle diameter, measured by the method described in [Measurement of average particle diameter] of Example 1, was in the range of 7.5 to 8.5 μm, thereby obtaining the raw coal powder of Example 2. The volatile matter and true density of the raw coal powder of Example 2 were determined in the same manner as in Example 1. The results are shown in Table 1.
[0121] ≪Process D≫ The raw coal powder of Example 2 was graphitized in the same manner as in Example 1 to obtain an artificial graphite material for a negative electrode of a lithium ion secondary battery of Example 2. The average particle size of the artificial graphite material for the negative electrode of a lithium ion secondary battery of Example 2 was calculated by the method described in [Measurement of average particle size] above. The results are shown in Table 1.
[0122] Example 3 <Production of raw material oil composition> The saturated fraction of the fluid catalytic cracking residue obtained in Example 1 and the aromatic fraction of the fluid catalytic cracking residue were mixed in a mass ratio of 70:30 to obtain a stock oil composition of Example 3. The normal paraffin content and aromatics index fa of the base oil composition of Example 3 were determined by the same methods as in Example 1. The results are shown in Table 1.
[0123] ≪Process A≫ The raw oil composition of Example 3 was coked by the same coking treatment as in Example 1 to obtain a raw coal composition of Example 3.
[0124] ≪Process B≫ The raw coke composition of Example 3 was heated at 600° C. in a mixed gas flow having a volume ratio of nitrogen and oxygen of 90:10, to obtain a heat-treated raw coke composition of Example 3. The heat treatment method was as follows: heating from room temperature (25°C) to 600°C in 1 hour and 30 minutes, holding at 600°C for 1 hour, and cooling from 600°C to 400°C in 1 hour and 30 minutes. After 400°C, the mixture was left to cool for 4 hours while continuing to flow with the mixed gas.
[0125] ≪Process C≫ The heat-treated raw coal composition of Example 3 was pulverized in an air-flow jet mill so that the average particle diameter, measured by the method described in [Measurement of average particle diameter] of Example 1, was in the range of 7.5 to 8.5 μm, thereby obtaining the raw coal powder of Example 3. The volatile matter and true density of the raw coal powder of Example 3 were determined in the same manner as in Example 1. The results are shown in Table 1.
[0126] ≪Process D≫ The raw coal powder of Example 3 was graphitized in the same manner as in Example 1 to obtain an artificial graphite material for a negative electrode of a lithium ion secondary battery of Example 3. The average particle size of the artificial graphite material for the negative electrode of a lithium ion secondary battery of Example 3 was calculated by the method described in [Measurement of average particle size] above. The results are shown in Table 1.
[0127] Example 4 <Production of raw material oil composition> The saturated fraction of the vacuum distillation residual oil obtained in Example 1 and the aromatic fraction of the fluid catalytic cracking residual oil also obtained in Example 1 were mixed in a mass ratio of 30:70 to obtain the raw material oil composition of Example 4. The normal paraffin content and aromatics index fa of the base oil composition of Example 4 were determined by the same methods as in Example 1. The results are shown in Table 1.
[0128] ≪Process A≫ The raw oil composition of Example 4 was coked by the same coking treatment as in Example 1 to obtain a raw coal composition of Example 4.
[0129] ≪Process B≫ The raw coke composition of Example 4 was heated at 500° C. in a mixed gas flow having a nitrogen and oxygen volume ratio of 83:17, to obtain a heat-treated raw coke composition of Example 4. The heat treatment method was as follows: heating from room temperature to 500°C for 1 hour, holding at 500°C for 1 hour, and cooling from 500°C to 400°C for 1 hour. After 400°C, the material was left to cool for 4 hours while continuing the flow of the mixed gas.
[0130] ≪Process C≫ The heat-treated raw coal composition of Example 4 was pulverized in an air-flow jet mill so that the average particle diameter, measured by the method described in [Measurement of average particle diameter] of Example 1, was in the range of 7.5 to 8.5 μm, thereby obtaining the raw coal powder of Example 4. The volatile matter and true density of the raw coal powder of Example 4 were determined in the same manner as in Example 1. The results are shown in Table 1.
[0131] ≪Process D≫ The raw coal powder of Example 4 was graphitized in the same manner as in Example 1 to obtain an artificial graphite material for a negative electrode of a lithium ion secondary battery of Example 4. The average particle size of the artificial graphite material for the negative electrode of a lithium ion secondary battery of Example 4 was calculated by the method described in [Measurement of average particle size] above. The results are shown in Table 1.
[0132] Example 5 <Production of raw material oil composition> The saturated fraction of the fluid catalytic cracking residual oil obtained in Example 1, the aromatic fraction of the fluid catalytic cracking residual oil also obtained in Example 1, and the hydrodesulfurized oil obtained in Example 2 were mixed in a mass ratio of 20:20:60 to obtain the feedstock oil composition of Example 5. The normal paraffin content and aromatics index fa in the base oil composition of Example 5 were determined by the same methods as in Example 1. The results are shown in Table 1.
[0133] ≪Process A≫ The raw oil composition of Example 5 was coked by the same coking treatment as in Example 1 to obtain a raw coal composition of Example 5.
[0134] ≪Process B≫ The raw coke composition of Example 5 was heated at 500° C. in a mixed gas flow having a nitrogen / oxygen volume ratio of 83:17, to obtain a heat-treated raw coke composition of Example 5. The heat treatment method was as follows: heating from room temperature (25°C) to 500°C for 1 hour, holding at 500°C for 1 hour, and cooling from 500°C to 400°C for 1 hour. After 400°C, the material was left to cool for 4 hours while continuing the flow of the mixed gas.
[0135] ≪Process C≫ The heat-treated raw coal composition of Example 5 was pulverized in an air-flow jet mill so that the average particle diameter, measured by the method described in [Measurement of average particle diameter] of Example 1, was in the range of 7.5 to 8.5 μm, thereby obtaining the raw coal powder of Example 5. The volatile matter and true density of the raw coal powder of Example 5 were determined in the same manner as in Example 1. The results are shown in Table 1.
[0136] ≪Process D≫ The raw coal powder of Example 5 was graphitized in the same manner as in Example 1 to obtain an artificial graphite material for a negative electrode of a lithium ion secondary battery of Example 5. The average particle size of the artificial graphite material for the negative electrode of a lithium ion secondary battery of Example 5 was calculated by the method described in [Measurement of average particle size] above. The results are shown in Table 1.
[0137] Comparative Example 1 <Preparation of raw material oil composition> As the raw coke composition of Comparative Example 1, the same raw coke composition as that of Example 1 was used.
[0138] ≪Process A≫ The raw coke composition of Comparative Example 1 was coked by the same coking treatment as in Example 1 to obtain a raw coke composition of Comparative Example 1.
[0139] <Low temperature heat treatment process> The raw coke composition of Comparative Example 1 was heated at 400° C. in a mixed gas flow having a nitrogen and oxygen volume ratio of 83:17, to obtain a heat-treated raw coke composition of Comparative Example 1. The heat treatment method consisted of increasing the temperature from room temperature (25°C) to 400°C for 1 hour, maintaining the temperature at 400°C for 1 hour, and then allowing the material to cool for 4 hours while continuing the flow of the mixed gas.
[0140] ≪Process C≫ The heat-treated raw coal composition of Comparative Example 1 was pulverized in an air-flow jet mill so that the average particle diameter, measured by the method described in [Measurement of average particle diameter] of Example 1, was in the range of 7.5 to 8.5 μm, thereby obtaining the raw coal powder of Comparative Example 1. The volatile matter and true density of the raw coal powder of Comparative Example 1 were determined in the same manner as in Example 1. The results are shown in Table 1.
[0141] ≪Process D≫ The raw coal powder of Comparative Example 1 was graphitized in the same manner as in Example 1 to obtain an artificial graphite material for a negative electrode of a lithium ion secondary battery of Comparative Example 1. The average particle size of the artificial graphite material for lithium ion secondary battery negative electrodes of Comparative Example 1 was calculated by the method described in [Measurement of average particle size] above. The results are shown in Table 1.
[0142] Comparative Example 2 <Preparation of raw oil composition> As the raw coke composition of Comparative Example 2, the same raw coke composition as that of Example 1 was used.
[0143] ≪Process A≫ The raw coke composition of Comparative Example 2 was coked by the same coking treatment as in Example 1 to obtain a raw coke composition of Comparative Example 2.
[0144] <High-temperature heat treatment process> The raw coke composition of Comparative Example 2 was heated at 750° C. in a mixed gas flow having a nitrogen and oxygen volume ratio of 99:1 to obtain a heat-treated raw coke composition of Comparative Example 2. The heat treatment method was as follows: the temperature was increased from room temperature (25°C) to 750°C for 2 hours, held at 750°C for 1 hour, and decreased from 750°C to 400°C for 2 hours. After 400°C, the mixture was allowed to cool for 4 hours while the gas mixture was continued to flow. After that, the mixture was allowed to cool for 4 hours while the gas mixture was continued to flow.
[0145] ≪Process C≫ The heat-treated raw coal composition of Comparative Example 2 was pulverized in an air-flow jet mill so that the average particle diameter, measured by the method described in [Measurement of average particle diameter] in Example 1, was in the range of 7.5 to 8.5 μm, thereby obtaining the raw coal powder of Comparative Example 2. The volatile matter and true density of the raw coal powder of Comparative Example 2 were determined in the same manner as in Example 1. The results are shown in Table 1.
[0146] ≪Process D≫ The raw coal powder of Comparative Example 2 was graphitized in the same manner as in Example 1 to obtain an artificial graphite material for a negative electrode of a lithium ion secondary battery of Comparative Example 2. The average particle size of the artificial graphite material for lithium ion secondary battery negative electrodes of Comparative Example 2 was calculated by the method described in [Measurement of average particle size] above. The results are shown in Table 1.
[0147] Comparative Example 3 <Production of raw material oil composition> As the raw coke composition of Comparative Example 3, the same raw coke composition as that of Example 1 was used.
[0148] ≪Process A≫ The raw coke composition of Comparative Example 3 was coked by the same coking treatment as in Example 1 to obtain a raw coke composition of Comparative Example 3.
[0149] <Heat treatment process> In the method for producing an artificial graphite material for a lithium ion secondary battery negative electrode of Comparative Example 3, the raw coke composition was not subjected to a heat treatment.
[0150] ≪Process C≫ The raw coke composition of Comparative Example 3 was pulverized in an air jet mill so that the average particle diameter, measured by the method described in [Measurement of average particle diameter] in Example 1, was in the range of 7.5 to 8.5 μm, thereby obtaining the raw coke powder of Comparative Example 3. The volatile matter and true density of the raw coal powder of Comparative Example 3 were determined in the same manner as in Example 1. The results are shown in Table 1.
[0151] ≪Process D≫ The raw coal powder of Comparative Example 3 was graphitized in the same manner as in Example 1 to obtain an artificial graphite material for a negative electrode of a lithium ion secondary battery of Comparative Example 3. The average particle size of the artificial graphite material for a lithium ion secondary battery negative electrode of Comparative Example 3 was calculated by the method described in [Measurement of average particle size] above. The results are shown in Table 1.
[0152] Comparative Example 4 <Production of raw material oil composition> The aromatic fraction of the fluid catalytic cracking residual oil obtained in Example 1, the saturated fraction of the fluid catalytic cracking residual oil obtained in Example 1, and the hydrodesulfurized oil obtained in Example 2 were mixed in a mass ratio of 15:20:65 to obtain the raw material oil composition of Comparative Example 4. The normal paraffin content and aromatic index fa of the base oil composition of Comparative Example 4 were determined by the same methods as in Example 1. The results are shown in Table 1.
[0153] ≪Process A≫ The raw coke composition of Comparative Example 4 was coked by the same coking treatment as in Example 1 to obtain a raw coke composition of Comparative Example 4.
[0154] ≪Process B≫ The raw coke composition of Comparative Example 4 was heated at 500° C. in a mixed gas flow having a nitrogen and oxygen volume ratio of 83:17, to obtain a heat-treated raw coke composition of Comparative Example 4. The heat treatment method was as follows: heating from room temperature (25°C) to 500°C for 1 hour, holding at 500°C for 1 hour, and cooling from 500°C to 400°C for 1 hour. After 400°C, the material was left to cool for 4 hours while continuing the flow of the mixed gas.
[0155] ≪Process C≫ The heat-treated raw coal composition of Comparative Example 4 was pulverized in an air-flow jet mill so that the average particle diameter, measured by the method described in [Measurement of average particle diameter] in Example 1, was in the range of 7.5 to 8.5 μm, thereby obtaining the raw coal powder of Comparative Example 4. The volatile matter and true density of the raw coal powder of Comparative Example 4 were determined in the same manner as in Example 1. The results are shown in Table 1.
[0156] ≪Process D≫ The raw coal powder of Comparative Example 4 was graphitized in the same manner as in Example 1 to obtain an artificial graphite material for a negative electrode of a lithium ion secondary battery of Comparative Example 4. The average particle size of the artificial graphite material for lithium ion secondary battery negative electrodes of Comparative Example 4 was calculated by the method described in [Measurement of average particle size] above. The results are shown in Table 1.
[0157] Comparative Example 5 <Production of raw material oil composition> The aromatic fraction of the fluid catalytic cracking residue obtained in Example 1 and the saturated fraction of the fluid catalytic cracking residue also obtained in Example 1 were mixed in a mass ratio of 50:50 to obtain a raw material oil composition of Comparative Example 5. The normal paraffin content and aromatics index fa of the base oil composition of Comparative Example 5 were determined by the same methods as in Example 1. The results are shown in Table 1.
[0158] ≪Process A≫ The raw oil composition of Comparative Example 5 was coked by the same coking treatment as in Example 1 to obtain a raw coal composition of Comparative Example 5.
[0159] ≪Process B≫ The raw coke composition of Comparative Example 5 was heated at 700° C. in a mixed gas flow having a nitrogen and oxygen volume ratio of 98:2 to obtain a heat-treated raw coke composition of Comparative Example 5. The heat treatment method was as follows: the temperature was increased from room temperature (25°C) to 700°C for 2 hours, held at 700°C for 1 hour, and decreased from 700°C to 400°C for 2 hours. After 400°C, the material was allowed to cool for 4 hours while continuing the flow of the mixed gas.
[0160] ≪Process C≫ The heat-treated raw coal composition of Comparative Example 5 was pulverized in an air-flow jet mill so that the average particle diameter, measured by the method described in [Measurement of average particle diameter] in Example 1, was in the range of 7.5 to 8.5 μm, thereby obtaining the raw coal powder of Comparative Example 5. The volatile matter and true density of the raw coal powder of Comparative Example 5 were determined in the same manner as in Example 1. The results are shown in Table 1.
[0161] ≪Process D≫ The raw coal powder of Comparative Example 5 was graphitized in the same manner as in Example 1 to obtain an artificial graphite material for a negative electrode of a lithium ion secondary battery of Comparative Example 5. The average particle size of the artificial graphite material for a lithium ion secondary battery negative electrode of Comparative Example 5 was calculated by the method described in [Measurement of average particle size] above. The results are shown in Table 1.
[0162] Comparative Example 6 <Production of raw material oil composition> The saturated fraction of the vacuum distillation bottom oil obtained in Example 1 and the aromatic fraction of the fluid catalytic cracking bottom oil obtained in Example 1 were mixed in a mass ratio of 15:85 to obtain a stock oil composition of Comparative Example 6. The normal paraffin content and aromatics index fa of the base oil composition of Comparative Example 6 were determined by the same methods as in Example 1. The results are shown in Table 1.
[0163] ≪Process A≫ The raw oil composition of Comparative Example 6 was coked by the same coking treatment as in Example 1 to obtain a raw coal composition of Comparative Example 6.
[0164] ≪Process B≫ The raw coke composition of Comparative Example 6 was heated at 600° C. in a mixed gas flow having a nitrogen and oxygen volume ratio of 90:10, to obtain a heat-treated raw coke composition of Comparative Example 6. The heat treatment method was as follows: heating from room temperature (25°C) to 600°C in 1 hour and 30 minutes, holding at 600°C for 1 hour, and cooling from 600°C to 400°C in 1 hour and 30 minutes. After 400°C, the mixture was left to cool for 4 hours while continuing to flow with the mixed gas.
[0165] ≪Process C≫ The heat-treated raw coal composition of Comparative Example 6 was pulverized in an air-flow jet mill so that the average particle diameter, measured by the method described in [Measurement of average particle diameter] in Example 1, was in the range of 7.5 to 8.5 μm, thereby obtaining the raw coal powder of Comparative Example 6. The volatile matter and true density of the raw coal powder of Comparative Example 6 were determined in the same manner as in Example 1. The results are shown in Table 1.
[0166] ≪Process D≫ The raw coal powder of Comparative Example 6 was graphitized in the same manner as in Example 1 to obtain an artificial graphite material for a negative electrode of a lithium ion secondary battery of Comparative Example 6. The average particle size of the artificial graphite material for lithium ion secondary battery negative electrodes of Comparative Example 6 was calculated by the method described in [Measurement of average particle size] above. The results are shown in Table 1.
[0167] Comparative Example 7 <Production of raw material oil composition> The saturated fraction of the vacuum distillation residual oil obtained in Example 1, the aromatic fraction of the fluid catalytic cracking residual oil obtained in Example 1, and the hydrodesulfurized oil obtained in Example 2 were mixed in a mass ratio of 4:91:5 to obtain a stock oil composition of Comparative Example 7. The normal paraffin content and aromatic index fa of the stock oil composition of Comparative Example 7 were determined by the same method as in Example 1. The results are shown in Table 1.
[0168] ≪Process A≫ The raw oil composition of Comparative Example 7 was coked by the same coking treatment as in Example 1 to obtain a raw coal composition of Comparative Example 7.
[0169] ≪Process B≫ The raw coke composition of Comparative Example 7 was heated at 650° C. in a mixed gas flow having a nitrogen and oxygen volume ratio of 94:6 to obtain a heat-treated raw coke composition of Comparative Example 7. The heat treatment method was as follows: heating from room temperature (25°C) to 650°C in 1 hour and 30 minutes, holding at 650°C for 1 hour, and cooling from 650°C to 400°C in 1 hour and 30 minutes. After 400°C, the material was allowed to cool for 4 hours while continuing the flow of the mixed gas.
[0170] ≪Process C≫ The heat-treated raw coal composition of Comparative Example 7 was pulverized in an air-flow jet mill so that the average particle diameter, measured by the method described in [Measurement of average particle diameter] in Example 1, was in the range of 7.5 to 8.5 μm, thereby obtaining the raw coal powder of Comparative Example 7. The volatile matter and true density of the raw coal powder of Comparative Example 7 were determined in the same manner as in Example 1. The results are shown in Table 1.
[0171] ≪Process D≫ The raw coal powder of Comparative Example 7 was graphitized in the same manner as in Example 1 to obtain an artificial graphite material for a negative electrode of a lithium ion secondary battery of Comparative Example 7. The average particle size of the artificial graphite material for a lithium ion secondary battery negative electrode of Comparative Example 7 was calculated by the method described in [Measurement of average particle size] above. The results are shown in Table 1.
[0172] Comparative Example 8 The aromatic content of the fluid catalytic cracking residual oil obtained in Example 1 and the hydrodesulfurized oil obtained in Example 2 were mixed in a mass ratio of 15:85 to obtain a stock oil composition of Comparative Example 8. The normal paraffin content and aromatics index fa of the base oil composition of Comparative Example 8 were determined by the same methods as in Example 1. The results are shown in Table 1.
[0173] ≪Process A≫ The raw oil composition of Comparative Example 8 was coked by the same coking treatment as in Example 1 to obtain a raw coal composition of Comparative Example 8.
[0174] <Heat treatment process> The raw coke composition of Comparative Example 8 was heated at 550° C. in a mixed gas flow having a nitrogen and oxygen volume ratio of 83:17, to obtain a heat-treated raw coke composition of Comparative Example 8. The heat treatment method was as follows: heating from room temperature (25°C) to 550°C for 1 hour, holding at 550°C for 1 hour, and cooling from 550°C to 400°C for 1 hour. After 400°C, the material was left to cool for 4 hours while continuing the flow of the mixed gas.
[0175] ≪Process C≫ The heat-treated raw coal composition of Comparative Example 8 was pulverized in an air-flow jet mill so that the average particle diameter, measured by the method described in [Measurement of average particle diameter] in Example 1, was in the range of 7.5 to 8.5 μm, thereby obtaining the raw coal powder of Comparative Example 8. The volatile matter and true density of the raw coal powder of Comparative Example 8 were determined in the same manner as in Example 1. The results are shown in Table 1.
[0176] ≪Process D≫ The raw coal powder of Comparative Example 8 was graphitized in the same manner as in Example 1 to obtain an artificial graphite material for a negative electrode of a lithium ion secondary battery of Comparative Example 8. The average particle size of the artificial graphite material for a lithium ion secondary battery negative electrode of Comparative Example 8 was calculated by the method described in [Measurement of average particle size] above. The results are shown in Table 1.
[0177] Example 6 The artificial graphite material for lithium ion secondary battery negative electrodes obtained in Example 1 and the artificial graphite material for lithium ion secondary battery negative electrodes obtained in Comparative Example 3 were mixed in a mass ratio of 50:50 to obtain an artificial graphite material for lithium ion secondary battery negative electrodes of Example 6.
[0178] Example 7 The artificial graphite material for lithium ion secondary battery negative electrodes obtained in Example 1 and the artificial graphite material for lithium ion secondary battery negative electrodes obtained in Comparative Example 3 were mixed in a mass ratio of 30:70 to obtain an artificial graphite material for lithium ion secondary battery negative electrodes of Example 7.
[0179] Example 8 The artificial graphite material for lithium ion secondary battery negative electrodes obtained in Example 1 and the artificial graphite material for lithium ion secondary battery negative electrodes obtained in Comparative Example 3 were mixed in a mass ratio of 20:80 to obtain an artificial graphite material for lithium ion secondary battery negative electrodes of Example 8.
[0180] Example 9 <Production of raw oil composition, steps A and B> As the raw coke composition of Example 9, the same raw coke composition as that of Example 1 was used. The raw coke composition of Example 9 was coked by the same coking treatment as in Example 1 to obtain a raw coke composition of Example 9. The raw coke composition of Example 9 was subjected to the same heat treatment as in Example 1 to obtain a heat-treated raw coke composition of Example 9.
[0181] ≪Process C≫ The heat-treated raw coal composition of Example 9 was pulverized in an air-flow jet mill so that the average particle diameter, measured by the method described in [Measurement of average particle diameter] of Example 1, was in the range of 11.5 to 12.0 μm, to obtain the raw coal powder of Example 9. The volatile matter and true density of the raw coal powder of Example 9 were determined in the same manner as in Example 1. The results are shown in Table 1.
[0182] ≪Process D≫ The raw coal powder of Example 9 was graphitized in the same manner as in Example 1 to obtain an artificial graphite material for a negative electrode of a lithium ion secondary battery of Example 9. The average particle size of the artificial graphite material for the negative electrode of a lithium ion secondary battery of Example 9 was calculated by the method described in [Measurement of average particle size] above. The results are shown in Table 1.
[0183] Example 10 <Production of raw oil composition, steps A and B> As the raw coke composition of Example 10, the same raw coke composition as that of Example 1 was used. The raw coke composition of Example 10 was coked by the same coking treatment as in Example 1 to obtain the raw coke composition of Example 10. The raw coke composition of Example 10 was subjected to the same heat treatment as in Example 1 to obtain a heat-treated raw coke composition of Example 10.
[0184] ≪Process C≫ The heat-treated raw coal composition of Example 10 was pulverized in an air-flow jet mill so that the average particle diameter, measured by the method described in [Measurement of average particle diameter] of Example 1, was in the range of 2.5 to 3.5 μm, thereby obtaining the raw coal powder of Example 10. The volatile matter and true density of the raw coal powder of Example 10 were determined in the same manner as in Example 1. The results are shown in Table 1.
[0185] ≪Process D≫ The raw coal powder of Example 10 was graphitized in the same manner as in Example 1 to obtain an artificial graphite material for a negative electrode of a lithium ion secondary battery of Example 10. The average particle size of the artificial graphite material for the negative electrode of a lithium ion secondary battery of Example 10 was calculated by the method described in [Measurement of average particle size] above. The results are shown in Table 1.
[0186] Comparative Example 9 <Production of raw oil composition, steps A and B> As the raw coke composition of Comparative Example 9, the same raw coke composition as that of Example 1 was used. The raw coke composition of Comparative Example 9 was coked by the same coking treatment as in Example 1 to obtain a raw coke composition of Comparative Example 9. The raw coke composition of Comparative Example 9 was subjected to the same heat treatment as in Example 1 to obtain a heat-treated raw coke composition of Comparative Example 9.
[0187] <Crushing process> The heat-treated raw coal composition of Comparative Example 9 was pulverized in an air-flow jet mill so that the average particle diameter, measured by the method described in [Measurement of average particle diameter] in Example 1, was in the range of 12.0 to 13.0 μm, thereby obtaining the raw coal powder of Comparative Example 9. The volatile matter and true density of the raw coal powder of Comparative Example 9 were determined in the same manner as in Example 1. The results are shown in Table 1.
[0188] ≪Process (D)≫ The raw coal powder of Comparative Example 9 was graphitized in the same manner as in Example 1 to obtain an artificial graphite material for a negative electrode of a lithium ion secondary battery of Comparative Example 9. The average particle size of the artificial graphite material for a lithium ion secondary battery negative electrode of Comparative Example 9 was calculated by the method described in [Measurement of average particle size] above. The results are shown in Table 1.
[0189] Comparative Example 10 <Production of raw oil composition, steps A and B> As the raw coke composition of Comparative Example 10, the same raw coke composition as that of Example 1 was used. The raw coke composition of Comparative Example 10 was coked by the same coking treatment as in Example 1 to obtain a raw coke composition of Comparative Example 10. The raw coke composition of Comparative Example 10 was subjected to the same heat treatment as in Example 1 to obtain a heat-treated raw coke composition of Comparative Example 10.
[0190] <Crushing process> The heat-treated raw coal composition of Comparative Example 10 was pulverized in an air-flow jet mill so that the average particle diameter, measured by the method described in [Measurement of average particle diameter] in Example 1, was in the range of 14.0 to 15.0 μm, thereby obtaining the raw coal powder of Comparative Example 10. The volatile matter and true density of the raw coal powder of Comparative Example 10 were determined in the same manner as in Example 1. The results are shown in Table 1.
[0191] ≪Process (D)≫ The raw coal powder of Comparative Example 10 was graphitized in the same manner as in Example 1 to obtain an artificial graphite material for a negative electrode of a lithium ion secondary battery of Comparative Example 10. The average particle size of the artificial graphite material for a lithium ion secondary battery negative electrode of Comparative Example 10 was calculated by the method described in [Measurement of average particle size] above. The results are shown in Table 1.
[0192] <Preparation of evaluation battery> 1 was fabricated as an evaluation battery by the method described below. The negative electrode 11, negative electrode current collector 12, positive electrode 13, positive electrode current collector 14, and separator 15 used were as follows.
[0193] (Negative electrode 11, negative electrode current collector 12) Any of the artificial graphite materials for lithium ion secondary battery negative electrodes obtained in Examples 1 to 10 and Comparative Examples 1 to 10, an aqueous solution of carboxymethyl cellulose (CMC (BSH-6 manufactured by Dai-ichi Kogyo Seiyaku Co., Ltd.)) as a binder adjusted to a concentration of 1.5 mass %, and an aqueous solution in which styrene butadiene rubber (SBR) as a binder was dispersed at a concentration of 48 mass % were mixed in a solid content mass ratio of 98:1:1 to obtain a paste-like negative electrode mixture. The obtained negative electrode mixture was applied to the entire surface of one side of a copper foil having a thickness of 18 μm as a negative electrode current collector 12, and then dried and rolled to obtain a negative electrode sheet in which a negative electrode 11, which is a layer made of the negative electrode mixture, was formed on the negative electrode current collector 12. The amount of the negative electrode mixture applied per unit area on the negative electrode sheet is approximately 10 mg / cm2 in terms of the mass of the graphite material. 2 It was adjusted so that
[0194] Thereafter, the negative electrode sheet was cut to a width of 32 mm and a length of 52 mm. A part of the negative electrode 11 was then scraped off in a direction perpendicular to the longitudinal direction of the sheet to expose the negative electrode current collector 12 that served as a negative electrode lead plate.
[0195] (Positive electrode 13, positive electrode current collector 14) The positive electrode material, a nickel-cobalt-manganese-lithium composite oxide NCM523 (manufactured by Beijing Easpring Material Technology Co., Ltd.) with an average particle size of 12 μm, polyvinylidene fluoride (KF#1120 manufactured by Kureha Corporation) as a binder, and acetylene black (Denka Black (registered trademark) manufactured by Denka Co., Ltd.) as a conductive additive were mixed in a mass ratio of 89:6:5, and N-methyl-2-pyrrolidinone was added as a solvent and kneaded to obtain a paste-like positive electrode mixture. The obtained positive electrode mixture was applied to the entire surface of one side of an aluminum foil having a thickness of 30 μm as a positive electrode current collector 14, and then dried and rolled to obtain a positive electrode sheet in which a positive electrode 13, which is a layer made of the positive electrode mixture, was formed on the positive electrode current collector 14. The amount of the positive electrode mixture applied per unit area on the positive electrode sheet was approximately 17.2 mg / cm2 (mass of NCM523). 2 It was adjusted so that
[0196] Thereafter, the positive electrode sheet was cut to a width of 30 mm and a length of 50 mm. A part of the positive electrode 13 was then scraped off in a direction perpendicular to the longitudinal direction of the sheet to expose the positive electrode current collector 14 that served as a positive electrode lead plate.
[0197] (Separator 15) As the separator 15, a cellulose-based nonwoven fabric (TF40-50 manufactured by Nippon Koshi Co., Ltd.) was used. In order to produce the lithium ion secondary battery 10 shown in FIG. 1, first, a negative electrode sheet in which the negative electrode 11, the negative electrode current collector 12, and the negative electrode lead plate are integrated, a positive electrode sheet in which the positive electrode 13, the positive electrode current collector 14, and the positive electrode lead plate are integrated, the separator 15, and other members used in the lithium ion secondary battery 10 were dried. Specifically, the negative electrode sheet and the positive electrode sheet were dried at 120° C. under reduced pressure for 12 hours or more. In addition, the separator 15 and other members were dried at 70° C. under reduced pressure for 12 hours or more.
[0198] Next, the dried negative electrode sheet, positive electrode sheet, separator 15, and other members were assembled in an argon gas circulating glove box in which the dew point was controlled to -60°C or less. As a result, a single-layer electrode body was obtained in which the positive electrode 13 and the negative electrode 11 were laminated facing each other with the separator 15 interposed therebetween, and fixed with polyimide tape (not shown), as shown in Figure 1. The negative electrode sheet and the positive electrode sheet were laminated such that the peripheral portion of the laminated positive electrode sheet was surrounded by the inner peripheral portion of the negative electrode sheet.
[0199] Next, the single-layer electrode body was housed in an aluminum laminate exterior 16, and an electrolyte was injected into the interior. The electrolyte was prepared by dissolving lithium hexafluorophosphate (LiPF6) as an electrolyte in a solvent to a concentration of 1 mol / L, and further mixing vinylene carbonate (VC) to a concentration of 1 mass %. The solvent used was a mixture of ethylene carbonate (EC), dimethyl carbonate (DMC), and diethyl carbonate (DEC) in a volume ratio of 15:70:15.
[0200] Thereafter, with the positive electrode lead plate and the negative electrode lead plate protruding, the aluminum laminate exterior 16 was heat-sealed. By the above steps, the sealed lithium ion secondary batteries 10 of Examples 1 to 10 and Comparative Examples 1 to 10 were obtained.
[0201] <Charge and discharge test of evaluation battery> The lithium ion secondary batteries 10 of Examples 1 to 10 and Comparative Examples 1 to 10 were subjected to the charge / discharge tests shown below. First, a preliminary test was conducted to detect abnormalities in the battery. That is, the battery was placed in a constant temperature room at 25°C, and charged at a constant current of 4 mA until the battery voltage reached 4.2 V, and after a 10-minute pause, it was discharged at the same constant current until the battery voltage reached 3.0 V. This cycle of charging, pausing, and discharging was considered as one charge-discharge cycle, and the charge-discharge cycle was repeated three times under the same conditions to perform the preliminary test. This preliminary test confirmed that there were no abnormalities in all of the batteries of Examples 1 to 10 and Comparative Examples 1 to 10. Then, the main test described below was carried out. Note that the preliminary test is not included in the number of cycles in the main test.
[0202] In this test, the battery was placed in a constant temperature room at 25°C and subjected to constant current / constant voltage charging with a charging current of 30 mA, charging voltage of 4.2 V, and charging time of 3 hours, followed by a 10-minute pause and then constant current discharge at the same current (30 mA) until the battery voltage reached 3.0 V. This cycle of charging, pausing, and discharging constituted one charge / discharge cycle, and the charge / discharge cycle was repeated three times under the same conditions, with the discharge capacity in the third cycle being designated the "initial discharge capacity."
[0203] Next, in the same thermostatic chamber, the battery was charged at a constant current / constant voltage with a charging current of 135 mA, a charging voltage of 4.2 V, and a charging time of 3 hours, and then after a 10-minute pause, it was discharged at a constant current of 30 mA until the battery voltage reached 3.0 V. This cycle of charging, pausing, and discharging constituted one charge / discharge cycle, and the charge / discharge cycle was repeated 100 times under the same conditions. The battery was then placed in the same thermostatic chamber and left for 5 hours, after which the charge / discharge cycle was repeated three times under the same conditions as the charge / discharge cycle in which the initial discharge capacity was determined, and the discharge capacity in the third cycle was taken as the "discharge capacity after repeated rapid charging."
[0204] As an index showing the capacity degradation after repeated rapid charging, the retention rate (%) of the "discharge capacity after repeated rapid charging" to the above-mentioned "initial discharge capacity" was calculated using the following formula (1). The results are shown in Table 1.
[0205]
number
[0206] [Table 1]
[0207] As shown in Table 1, in the manufacturing methods of the artificial graphite materials for lithium ion secondary battery negative electrodes of Examples 1 to 5, 9 and 10, the volatile content was less than 3.71% and the true density was 1.22 g / cm 3 Super 1.73g / cm 3 The raw material coal powder used has an average particle size of less than 12.6 μm, and the final artificial graphite material for a lithium ion secondary battery negative electrode has an average particle size of less than 12.6 μm. The "discharge capacity retention rate (%) after repeated rapid charging" was 75% or more in the lithium ion secondary batteries of Examples 1 to 5, 9, and 10. From this, it was confirmed that the lithium ion secondary batteries using the negative electrodes containing the artificial graphite materials for lithium ion secondary battery negative electrodes of Examples 1 to 5, 9, and 10 are less likely to deteriorate in discharge capacity even when the lithium ion secondary batteries are repeatedly charged rapidly.
[0208] In addition, the volatile content is less than 3.71% and the true density is 1.22 g / cm 3 Super 1.73g / cm 3 In the lithium ion secondary batteries of Examples 6 to 8, which use negative electrodes that combine the artificial graphite material for lithium ion secondary battery negative electrodes of Example 1 in which raw coal powder within the range of less than 12.6 μm is used and in which the average particle size of the finally obtained artificial graphite material for lithium ion secondary battery negative electrodes is less than 12.6 μm, and another artificial graphite material whose volatile content and true density do not satisfy the above ranges (the artificial graphite material for lithium ion secondary battery negative electrodes of Comparative Example 3), the "discharge capacity retention rate (%) after repeated rapid charging" was 75% or more, and it was confirmed that the discharge capacity is not easily deteriorated even when rapid charging is repeated.
[0209] On the other hand, for the negative electrodes of the lithium ion secondary batteries of Comparative Examples 1, 3 and 8, artificial graphite materials for lithium ion secondary battery negative electrodes obtained using raw coal powder with a volatile content of 3.71% or more are used. The negative electrodes of the lithium ion secondary batteries of Comparative Examples 2 and 4 to 7 had a true density of 1.22 g / cm 3 Super 1.73g / cm 3 In the present invention, an artificial graphite material for the negative electrode of a lithium ion secondary battery obtained by using raw coal powder that is outside the above range is used.
[0210] Therefore, it was confirmed that the lithium ion secondary batteries of Comparative Examples 1 to 8 all had a lower "discharge capacity retention rate (%) after repeated rapid charging" than the lithium ion secondary batteries of Examples 1 to 8, and that the discharge capacity is prone to deterioration.
[0211] For the negative electrodes of the lithium ion secondary batteries of Comparative Examples 9 and 10, the volatile content and true density of the raw coal powder were the same as in Example 1, but the average particle size of the artificial graphite material for lithium ion secondary battery negative electrodes exceeded 12.6 μm, which is outside the range of the present invention.
[0212] Therefore, it was confirmed that the lithium ion secondary batteries of Comparative Examples 1 to 10 all had a lower "discharge capacity retention rate (%) after repeated rapid charging" than the lithium ion secondary batteries of Examples 1 to 10, and that the discharge capacity is prone to degradation. [Industrial Applicability]
[0213] A lithium ion secondary battery having a negative electrode containing the artificial graphite material obtained by the method for producing an artificial graphite material for a lithium ion secondary battery negative electrode according to the present invention is resistant to deterioration in discharge capacity even when rapidly charged repeatedly. Therefore, the lithium ion secondary battery having a negative electrode containing the artificial graphite material obtained by the method for producing an artificial graphite material for a lithium ion secondary battery negative electrode according to the present invention can be preferably used for electric vehicles, natural energy grid interconnection, and other industrial applications. [Explanation of symbols]
[0214] 10. Lithium-ion secondary battery 11...Negative electrode 12...Negative electrode current collector 13...Positive electrode 14...Positive electrode current collector 15. Separator 16 Aluminum laminate exterior
Claims
1. A method for producing an artificial graphite material for a negative electrode of a lithium ion secondary battery, comprising the steps of: coking the feed oil composition by a delayed coking process to produce a feed coal composition; heat-treating the raw coke composition to obtain a heat-treated raw coke composition; pulverizing the heat-treated raw coal composition to obtain raw coal powder; and graphitizing the raw coal powder to obtain an artificial graphite material for a lithium ion secondary battery negative electrode, The volatile content of the raw coal powder is less than 3.71%, The true density of the raw coal powder is 1.22 g / cm 3 Super 1.73g / cm 3 is less than The method for producing an artificial graphite material for a lithium ion secondary battery negative electrode, wherein the artificial graphite material for a lithium ion secondary battery negative electrode has an average particle diameter of less than 12.6 μm as measured by a laser diffraction particle size distribution measurement device.
2. 2. The method for producing an artificial graphite material for a lithium ion secondary battery negative electrode according to claim 1, wherein the maximum temperature reached in the heat treatment in the step of obtaining the heat-treated raw carbon composition is 500° C. or higher and 700° C. or lower.
3. 3. The method for producing an artificial graphite material for a lithium ion secondary battery negative electrode according to claim 1, wherein the raw oil composition has a normal paraffin content of 5 to 20 mass% based on a total amount of the raw oil composition, and an aromatic index fa determined by the Knight method of 0.3 to 0.
65.
4. The method for producing an artificial graphite material for a lithium ion secondary battery negative electrode according to any one of claims 1 to 3, wherein the average particle diameter of the artificial graphite material for a lithium ion secondary battery negative electrode is 3.1 µm or more and 11.8 µm or less.
Citation Information
Patent Citations
Preparation method of artificial graphite material special for lithium ion battery negative electrode
CN111825088A
JP1979015684A
Nonaqueous electrolyte secondary battery
JP1998027600A
Manufacture of graphite powder for lithium ion secondary battery negative electrode
JP2001023638A
Low-temperature burned carbon for material of electrode
JP2007019257A